Impacto de modelos alternativos de uso de rebocadores portuários no aumento da capacidade de navios - Soares, Leonardo Sousa (2017)
This work aims to present an innovating and alternative methodology of use of harbour tugs in assisting the ships’ maneuvers in ports, with the primary purpose of reducing the ship’s transit speed in the access channels to ports and terminals. This reduction of ship’s speed has the consequence of minimizing ship’s sinkage due to waves and squat effect as well. Moreover, such reduction in the ship’s sinkage is converted in an increase of the navigation parameter know as underkeel clearance value. Finally, the final purpose of the work is convert this increase of underkeel clearance in increase of ship’s draft, providing the ship’s owner an increase of cargo to be shipped and, in some cases, an increase of incomes, according to charter rates settled within a contract of affreightment, and tug’s charter prices. The proposed methodology can be used as a tool (in the decision-making process) by commercial directors or managers of ship’s companies, as well as port’s companies, which intends to remove port’s restrictions, by using harbour tugs in assisting ship’s maneuvers.